2021
DOI: 10.1001/jamapsychiatry.2021.0154
|View full text |Cite
|
Sign up to set email alerts
|

Association of US Nurse and Physician Occupation With Risk of Suicide

Abstract: IMPORTANCENurses are the largest component of the US health care workforce. Recent research suggests that nurses may be at high risk for suicide; however, few studies on this topic exist. OBJECTIVES To estimate the national incidence of suicide among nurses and examine characteristics of nurse suicides compared with physicians and the general population. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study used US data from 159 372 suicides reported in the National Violent Death Reporting System fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 26 publications
5
120
1
3
Order By: Relevance
“…Given prior work demonstrating high trauma exposure and psychiatric symptoms in FR 38 , including high rates of both suicidal thoughts and behaviors, particularly in EMS 39 , results highlight the importance of addressing the impact of working during a pandemic on FR. Similarly, findings underscored the higher CROS exposure and psychiatric distress in nurses as compared with physicians, building on prior work finding increased distress, suicidal ideation, and suicidal behavior specifically in nurses 40 .…”
Section: Discussionsupporting
confidence: 54%
“…Given prior work demonstrating high trauma exposure and psychiatric symptoms in FR 38 , including high rates of both suicidal thoughts and behaviors, particularly in EMS 39 , results highlight the importance of addressing the impact of working during a pandemic on FR. Similarly, findings underscored the higher CROS exposure and psychiatric distress in nurses as compared with physicians, building on prior work finding increased distress, suicidal ideation, and suicidal behavior specifically in nurses 40 .…”
Section: Discussionsupporting
confidence: 54%
“…It is anticipated that nurse's psychological burden will potentially increase in the context of the COVID‐19 global pandemic (Davis et al . 2021 ). Consequently, there has been a number of international studies exploring the psychological burden of healthcare workers during the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological burden has impacted between 12% and 67% of nurses during the COVID-19 pandemic (Vizheh et al 2020). Consequently, suicide rates among nurses are predicted to increase during the COVID-19 pandemic as a result of work-related stressors and mental health problems (Davis et al 2021). The monitoring and surveillance of clinician's mental health and associated workplace characteristics are critical (Jackson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Using the latest available data from the Centers for Disease Control and Prevention National Violent Death Reporting System, Davis et al (2021) found that between 2007 and 2018, nurses were 18% more likely to die from suicide than the general population. Among female nurses, the risk of death by suicide was approximately twice the risk observed in the general population, and 70% more likely than female physicians.…”
Section: The Alarming Evidencementioning
confidence: 99%
“…Rates of death by suicide among physicians did not differ signifi cantly from the general population. Davis et al (2021) also reported that from 2017 to 2018, an estimated 729 American nurses died by suicide, the highest reported number on record. But we fear the worst is yet to come.…”
Section: The Alarming Evidencementioning
confidence: 99%